Sleep Behavior and Self-Reported Infertility: A Cross-Sectional Analysis Among U.S. Women - Liang, Zhu; Liu, Jianqiao (Frontiers in Endocrinology, 2022)
Objective: To investigate the associations between sleep behaviors and female infertility. Methods: We conducted a cross-sectional study composed of 2175 U.S. women 18-44 years of age from the National Health and Nutrition Examination Survey (NHANES) (2015-2018). Bedtime /waketime and sleep duration were extracted from the sleep disorder questionnaire. Self-reported infertility was defined as a binary variable based on the participants’ response to the question, “Have you ever attempted to become pregnant over a period of at least a year without becoming pregnant?”. Multivariate logistic regression analyses were done to explore the relationship between sleep behaviors and female infertility. Results: Bedtime (OR=1.24; 95% CI, 1.10-1.40, P = 0.001) and waketime (OR=1.14; 95% CI, 1.01-1.28, P = 0.037) were associated with infertility. Waketime of 08:00 was the inflection point, above which the probability of infertility increased rapidly (OR=1.41; 95% CI, 1.11-1.79, P = 0.004). Sleep-wake behavior was significantly associated with infertility (OR=1.34; 95% CI, 1.16-1.53, P < 0.001) and participants with early-bed/early-rise behavior had the lowest risk. Conclusions: Among U.S. women 18-44 years of age, bedtime and waketime were significantly linearly and non-linearly correlated with infertility, respectively. Early-bed/early-rise behavior was associated with the lowest infertility rate. Further study is needed because the timing of sleep behaviors are modifiable factors and could be a novel strategy to cope with infertility.